Limits and prospects of photovoltaic covers in Mediterranean greenhouses - Alvaro Marucci (Journal of Agricultural Engineering, 2013)
The use of plastic film coverings has made a significant contribution to the development of greenhouses in Italy and to a new generation of greenhouses that differ from those of Central and Northern Europe: the so called Mediterranean Greenhouse. This is a simple structure with cheap coverings and emergency artificial heating systems. During the winter season, the available solar energy is more than sufficient to meet energy requirements. During the hot season, however, the intense solar radiation and the high air temperatures are problematic. Different active and passive strategies are, therefore, used to counteract this excessive energy intake with a considerable increase in costs. We believe that using this surplus energy to produce electricity would: i) provide an income from the sale of electricity; ii) allow the greenhouse to be used throughout the year; iii) reduce the costs of cooling the greenhouse. This paper aims to identify the energy surplus in relation to cultivation requirements that could be used to produce electricity with new and innovative solutions based on flexible and semi-transparent photovoltaic modules. The research was carried out with reference to the southern coast of the Lazio region, central Italy, by evaluating energy supply and demand to determine the surplus of solar energy produced in a greenhouse covered with double plastic film. Besides the shape of the greenhouse, the surplus depends on the covering material and the location. The degree of cloud cover and the type of cultivation carried out in the greenhouse also have an impact. We calculated the surplus energy under extreme conditions: clear sky and cloudy sky, and according to different crop species (tomato 12 months, tomato 8 months, aubergine 12 months). Results showed: i) the surplus of energy available in the greenhouse for the production of energy from new generation solar cells with varying degrees of sky coverage and crop species; ii) the times of the year in which there is an effective surplus of energy; iii) the most suitable crop cycles to achieve a surplus of solar energy to be exploited in the most convenient way.